2013
DOI: 10.3945/ajcn.113.059030
|View full text |Cite
|
Sign up to set email alerts
|

Dairy products and the risk of type 2 diabetes: a systematic review and dose-response meta-analysis of cohort studies

Abstract: This meta-analysis suggests that there is a significant inverse association between intakes of dairy products, low-fat dairy products, and cheese and risk of type 2 diabetes. Any additional studies should assess the association between other specific types of dairy products and the risk of type 2 diabetes and adjust for more confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
281
6
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(322 citation statements)
references
References 58 publications
22
281
6
13
Order By: Relevance
“…However, the potential health impacts of animal-derived foods, and more specifically Proceedings of the Nutrition Society milk and dairy consumption, have been questioned owing to their high saturated fat content (for review, see (3) ). However, emerging epidemiological evidence supports the beneficial effects of milk and dairy consumption on health, particularly cardiometabolic health (4)(5)(6) .…”
Section: Dairy Protein: Metabolic Health: Blood Pressure: Vascular Fumentioning
confidence: 99%
“…However, the potential health impacts of animal-derived foods, and more specifically Proceedings of the Nutrition Society milk and dairy consumption, have been questioned owing to their high saturated fat content (for review, see (3) ). However, emerging epidemiological evidence supports the beneficial effects of milk and dairy consumption on health, particularly cardiometabolic health (4)(5)(6) .…”
Section: Dairy Protein: Metabolic Health: Blood Pressure: Vascular Fumentioning
confidence: 99%
“…More recently, a systematic review and dose-response metaanalysis reported that a high intake of total dairy products was associated with a significant decrease in risk of T2DM (RR 0·89; 95 % CI 0·82, 0·96) and this reduction in risk was 7 % less for every 400 g total dairy product consumed per d (47) . In addition, significant inverse associations were also found for low-fat dairy products (RR 0·83; 95 % CI 0·76, 0·90), low-fat or skimmed milk (RR 0·82; 95 % CI 0·82, 0·69), cheese (RR 0·91; 95 % CI 0·84, 0·98) and yoghurt (RR 0·86; 95 % CI 0·75, 0·98), but not for high-fat dairy or total milk when high v. low consumption was compared.…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…In addition, inverse association between low-fat and fluid dairy food consumption and elevated blood pressure was found in a meta-analysis of cohort studies (15) . Aune et al (16) focused on dairy products and type 2 diabetes and concluded that there was an inverse association between consumption of total dairy product and low-fat dairy product, and risk of type 2 diabetes.…”
Section: Change Of the Status Of Metabolic Syndrome And Cancermentioning
confidence: 99%
“…Cancer has been the leading cause of death since 1983, and CVD and type 2 diabetes related to MetS also have been major causes of death (6) . These chronic diseases are well known to be associated with diet; many epidemiological studies have reported that meat consumption increased the risk of Proceedings of the Nutrition Society metabolic diseases and cancer (7)(8)(9)(10)(11) , while milk consumption reduced the risk (12)(13)(14)(15)(16) . Change of diet, especially increased consumption of meat and milk, seems closely related to higher rates of chronic diseases among Koreans.…”
mentioning
confidence: 99%